Principles of tourism 2 - Tuazon-Disimulacion, Maria Arlene (Bam) (Mandaluyong City : Books Atbp. Publishing Corp., 2016)
Its 18 chapters have been designed to help learners develop higher-order skills. The book is divided into three sections, namely, Introduction to tourism, tourism sectors, and special topics in tourism.
Part I : Overview of the tourism industry -- Chapter 1. Overview of the tourism industry -- Chapter 2. The tourism and hospitality professional -- Part II : Tourism sectors -- Chapter 3. Accommodations -- Chapter 4. Attractions -- Chapter 5. Food and beverage services -- Chapter 6. Gaming entertainment -- Chapter 7. Land transportation -- Chapter 8. Rail transport -- Chapter 9. Air transport and space tourism -- Chapter 10. Water transport and the cruise industry -- Chapter 11. M.I.C.E. and special events -- Chapter 12. Travel trade -- Chapter 13. Government -- Chapter 14. Associations, volunteers, communities, and lobbyists -- Chapter 15. Education -- Part III : Advanced topics in tourism -- Chapter 16. Tourism research, policy, planning, and development -- Chapter 17. Tourism marketing -- Chapter 18. Responsible tourism.
Includes bibliographical references.
Keywords: TOURISM INDUSTRY